The Relationship Between Social Support and Academic Stress Among Migrant University Students in Jakarta - Franky Pabianus; Novendawati Wahyu Sitasari; Deny Surya Saputra (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aimed to examine the relationship between perceived social support and academic stress among migrant university students in DKI Jakarta, Indonesia. Methodology: This study employed a quantitative correlational design involving 386 migrant university students selected through purposive sampling. Data were collected using the Student Life Stress Inventory (SLSI) and the Multidimensional Scale of Perceived Social Support (MSPSS). Validity and reliability tests were conducted, followed by normality testing using the Kolmogorov–Smirnov test. Because the data were not normally distributed, hypothesis testing was performed using Spearman’s rank correlation analysis. Main Findings: The results revealed a significant positive relationship between perceived social support and academic stress among migrant university students (r = 0.627, p < 0.05). The majority of respondents were categorized as having high levels of academic stress and high levels of perceived social support. The findings indicate that students reporting higher social support also tended to report higher academic stress. Novelty/Originality of this study: Previous studies generally reported that social support was associated with lower academic stress. In contrast, this study found a positive relationship between social support and academic stress among migrant university students in a metropolitan setting. The findings provide new insights into the psychosocial dynamics of migrant students and suggest that social support may coexist with heightened academic pressure in urban higher education environments.